Diversity Intelligence Integrating Diversity Intelligence alongside Intellectual, Emotional, and Cultural Intelligence for Leadership and Career Development - Hughes, Claretha (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
Organization leaders typically look at each job position, characterized as the same based on pay and job description, in the same way. They hire employees to do that particular job and often do not consider other capabilities that the employees may possess. This book examines how to optimize workforce performance by understanding the diversity of skills and competencies of employees. Diversity is generally explored in terms of gender, race, nationality, disability, and other physical characteristics that differentiate one legally protected group of people from another. In the workplace, however, diversity can take on a different meaning, describing not only physical differences but also work performance characteristics unique to each individual employee. Inter-personnel diversity seeks to explore those diverse characteristics and begin to understand each employee's strengths and weaknesses so that they can be developed to benefit the employee and the organization. This much-needed text will inform scholars and scholar-practitioners in HRD and workforce development how to use these differences to enhance the individual and the organization.